Tamir ve bakım kaynağı - Akdaş, Murat (Fen Bilimleri Enstitüsü, 1994)
Çeşitli aşınma türleri ile karşılaşan ve zorlanan parçalar kullanılmaz hale gelmeden önce, aşınan kısımlarının uygun alaşım ve kaynak yöntemi ile doldurulması sonucu parça ekonomik olarak tekrar kullanılabilir duruma getirilebileceği gibi etkiyen aşınmalara karşı dirençli olacak şekilde seçilmiş doldurma malzemesi sayesinde parçanın ömrü arttırılır. Bu da ancak kortıyucu tamir bakım yöntemlerinin uygulanması ile sağlanabilir. Bu çalışmada, tamir bakım kaynağının uygulanmasında dikkat edilmesi gereken hususlar ve uygulama adımları açıklanmaya çalışılmıştır. Bu amaçla öncelikle hasar ve aşınma mekanizmalarının oluşumu hakkında açıklayıcı bilgiler verilmiştir. Daha sonrada tamir kaynağının işlem adımları anlatılmıştır. Burada amaç, öncelikle hasarlı bölge ile ilgili bilgilerin sağlanması ve elde edilen bilgilerin değerlendirilerek kaynağın başarısının tahmin edilmesi ve karar verilmesidir. Bu aşamadan sonra, kaynağın teknolojik özellikleri belirlenmiştir. Bunlar; uygulanacak kaynak metodunun tespiti, kaynak için ilave malzeme tespiti, uygulanacak ısıl işlemin tespiti ve kaynak parametrelerinin tespitidir. Son bölümde ise, tamir ve bakım kaynağıyla ilgili problemlerin çözümleri ve yapılan uygulamalara ait bilgiler, parçaların kullanıldıkları çalışma alanlarımda kapsayacak bir şekilde sunulmuştur.

Many engineers have no welding problems; they simply replace worn or broken parts. Yet it is not uncommon for premature failure of one small part to shut down a whole production line. Even then, however, welding is only considered a necessary ' evil. Maintenance shop welding has gained a bad reputation becouse the welder is often left with the responsibility of attemting repairs without the proper information to perform the job. With the welder faced with an oil-soaked casting or unknown base metal and no specialist training, it is understandable why repair welding can start badly and deteriote steadly. Major savings are achieved using successful repair procedures designed by experts to avoid plant shutdown and even reduce expensive stocking of spare parts. These procedures allow repairs to shafts, gears, pumps, engine heads and blocs, and many other pieces of equipment to be tacled with confidence. The resons repair welding lacks formal recognition as an independent discipline include: - Engineers still believe cnly standard production welding techniques and procedures are available. - Few welding engineers specialise in repair welding. - Salesmen recommending unsuitable products while purpoting to offer specialist advice. A lack of repair welding training programs and authoritative publication. It is not unreasonable to state that the majority of weld repairs are undertaken by company maintenance departments and engineering companies offering general engineering services. Few- organisations specialize in this important dicipline. Why haven't more companies entered the repair welding field, especially since a reputable service can offer an economical and. reliable repair facility, with good financial reward? The lack of expert information is one of the main answers. Companies that have developed succesful procedures over many years are not inclined to share this information. Many sales companies, due to their own inexperience, tend to overemphasize the equipment and welding materials needed to establish a service. The main objective of welding repair is to extend the service life of a failed structure by using welding. In reality, there are two typical approaches to meeting this objective, research-oriented and pragmatic. In the former, the main emphasis is made on failure and stress analysis, which sometimes accounts for a disproportionately large portion of the repair budget. Study of the probable cause of failure turns into extensive failure and metallurgical analyses, and the determination of stresses in a failed area can become a complete and extended stress analysis. Unfortunately, the data obtained will rarely find their way into a repair approach or a welding procedure. However, it is often forgotten that in many cases the analysis, the main objective should be for the repair effort. Considering the high cost of such an analysis, the main objective should be to generate sufficient input data to support development of a comprehensive and realistic repair approach and welding procedure. Analysis stage is include teh detemination of the possible cause of failure and stress situation in the area to be repaired. For this resons, at the second stage failure and mechanisms of wear arc studied. Rear can be defined as the progressive loss of material resulting from mechanical interaction between to surfaces in contact. In general these surfaces are in relative motion, either sliding or rolling, and are under load. Wear occurs because of the local mechanical failure of highly-stressed interfacial zones and the failure mode will often be influenced by environmental factors. Thus, as in any bulk metal failure, we can expect the surface not to be able to bear a critical load, since it will tend to deteriorate by ductile or brittle microfractures, often helped by chemical action. Surface deterioration can lead to the production of wear particles by a series of events characterised by adhesion or particle transfer mechanisms or, in certain cases, by a surface-fatigue form of failure. These three mechanisms are referred to as adhesive, abresive and fatique wear, and are the most important. In all three cases, stress transfer is principally via a solid-solid interface, but fluids can also impose or transfer high streses when their impact velocity is high. Fluid erosion and cavitation are typical examples of fluid wear mechanisms. Chemical wear such as corrosion and oxidation, have been omitted from the list because environmental factors, such as chemical reaction, influence almost every aspect of wear and it is difficult to place this subject in a special isolated category. Chemical reaction does not itself constitute a wear mechanism; it Vll must usually be accompained by some mechanical action to remove the chemical effects interact with and influence a mechanical wear process, sometimes beneficially and sometimes adversely. Similary, temperature, impact, and load are not wear mechanisms per se. We have considered them as further environmental factors, constributing to the stresses and energy transmissions imparted to the surface during the basic wear mechanisms. Wear is classified according to the obvious mechanisms of damege, as follows: Adhesive wear, also called mechanical wear or friction, is based on the mechanism of microwelding and tearing of surface asperities (minute high spots on the material surface). Abrasive wear, basi.-d on the mechanism of removal of softer material by cutting action of harder material, is often aided by surface fatiquc and corrosion. Wear by erosion, is similar to the previous mechanism but the hard abresive particles are in suspension in a fluid (gas or liquid), and the rate of damege depends on the speed of the particles, their hardness, and the impinging angle against the attactcd surface (it does not depend on pressure, as in typical abrasion). Wear by surface fatigue, is characterised by the removal of particles due to applied cyclic stresses that form and propogate micro-cracks, resulting in the loosening of small portions of metal. This mechanism is also present in abrasion and is aided by corrosion. Chemical wear, (inculiding oxidation and corrasion) is the best studied of these mechanisms. Matter is lost by dissolution of the metal or chemical changes that produce easilly-removed brittle metal oxides, sulphates, etc. Experimentally, this classf ication has often proved cumbersome when used to describe the results of a laboratory test. At the third stage, repair welding procedure steps are determined, they includes providing all data for about worn area, data providing methods, determination of material type of worn area and heat treatment selection. After that evaluation of data which are obtained and deciding to weld are explained. The fourth stage is repair welding technology. In this stage firstly explained that how to set up a shop. When establishing a repair service in a maintenance vm department or home workshop, financial consideration are always important. Assessments should be made of the following: - If heavy items are to be welded some mechanical handling equipment is required. - Certain consunables produce hazardous fumes requiring fume-extraction equipment. - Hardenable or crack-prone materials need preheating. The equipment depends on the work to be handled. - Finishing techniques must seriously be considered. Many repairs will require only hand dressing, while others may need accurate machining. It is important that machine shops be acquainted with tecniques for machining welded components, as these differ from conventional methods. The company maintenance department may have these facilities available, while the home workshop will probably require only a few extras to provide such service. The steps in a weld repair are: nondestructive testing, base metal identification, heat treatment selection and welding technique, which will vary according to the nature of the repair. The fifth stage is performance of repair welding. It inculudes surface preparation before beginig to repair welding, performing welding failure and necessary treatment after repair welding. At the sixth stage, solutions are offered with specific examples for all wear mechanism, built up welding and metal powder spraying process are examined and also recommended solutions are explained for different material as follow: Friction (Adhesion); There are two ways to combat adhesion. One is choose two metals of different composition and correct hardness values, and the oyher is to sellect carefully a lubricant of appropriate viscosity and with additives which will react advantageously with the metal surfaces. Spesific allays developed for friction control produce a smooth surface finish, and in some cases, porosity for trapping larger quantities of the lubricant between the moving surfaces. In addition, the alloys are often chosen to react with the lubricant additives to form a soapy film which further assists adhesion resistance. Abrasion; in general, the ideal solution to abrasive wear is atough coating, the hardness of wich exceeds that of the abrading material. When this is not possible, opt for a material which presents a high proportion of very hard phases in a tough material. IX Erosion; ceramics are especially resistant to ersion owing to their hardness and cohesion. For this reason, hard ceramic type particles are employed in protective surfaces to reduce the effect of erosion. In the alloys, the size of hard diamax particles is chosen to be larger than that of the eroding particles, and the distance between the diamax particles, i.e. the area of softer- matrix exposed to the eroding medium, is smaller than the diameter of eroding particles. This prevent the diamax particles being loosened from the matrix. To provide a compact structure a tough material is chosen for the matrix to bind the particles strongly. Fatique; fatique cracs are one of the causes of failure öf materials that are worn by corrosion, abrasion, or (including pitting, spalling and fretting). These cracs are also a contributory factor in the loss of material from a bearing surface which has been hardened by carburising, nitriding and particullaiy by galvanising. In these case, some of the cracs, instead of propogating through the material, run transversal ly until they reach the surface again, thus producing pits. To owercome fatique, a usual requerement is a tough bearing surface.
Repair and maintenance welding
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Keywords: Kaynak; Kaynak teknolojisi; Onarım; Welding; Welding technology; Repair